Community, buen vivir and resistance in Puná (Mayéutica Revista Científica de Humanidades y Artes, 2025)
This text describes the problems caused by the shrimp industry on Puná Island, both in terms of social and environmental impacts. At the same time, it reviews some of the theoretical and conceptual categories related to community, territory and buen vivir, as strategies of resistance to modern capitalist development.In this sense, it analyzes the mechanisms used by the island's communities in defense of their territories, and how they also propose economic and political alternatives in favor of the community and the mangrove ecosystem.
Keywords: Community; territory; buen vivir; shrimp extractivism; mangrove ecosystem; Puná Island